Relevansi Nilai-Nilai Akhlak Islami dalam Membentuk Etika Digital dan Karakter Peserta Didik Sebagai Respon Terhadap Tantangan Disinformasi dan Cyberbullying Di Era 5.0 - Puji Rahayu; Muhammad Latif Nawawi (Program Studi Pendidikan Agama Islam IAIQI Al-Qur'an Al-Ittifaqiyah, 2025)
The Society 5.0 era demands that humans have strong character and morals to be able to use technology wisely. This study aims to analyze the relevance of Islamic moral values ​​in shaping digital ethics and student character in response to disinformation and cyberbullying. The method used is descriptive qualitative through literature review with thematic analysis. The results show that Islamic moral values ​​play a significant role in fostering ethical awareness, media responsibility, and critical thinking in the digital space, making them relevant to facing the moral challenges of the Society 5.0 era. This study provides important implications for the development of Islamic education in the Society 5.0 era, particularly in the context of shaping digital ethics and student character. Theoretically, this research affirms that Islamic moral values can be formulated as an Islamic digital ethics framework capable of bridging technological advancement with religious morality. Practically, Islamic educational institutions need to integrate these values into digital literacy curricula through contextual learning and teacher role-modeling. Collaboration between the government, educators, and parents is also essential in creating a morally grounded educational ecosystem. Socially, the implementation of Islamic moral values serves as a preventive measure against disinformation, cyberbullying, and other negative behaviors, while simultaneously fostering a generation of digitally literate Muslims with strong Islamic ethical awareness.